Emergency TAVI in a critically ill patient: A case report. Issue 2 (31st December 2020) - Papadopoulos, Konstantinos; Chrissoheris, Michael; Halapas, Antonios; Kourkoveli, Panagiota; Ozden Tok, Ozge; Spargias, Konstantinos
Abstract: Transcatheter aortic valve implantation is a safe procedure even in inoperable patients with multi‐organ failure and cardiogenic shock. In such cases, the heart team should be prepared to proceed to emergent implantation for timely and successful management of the patient. Abstract : Transcatheter aortic valve implantation is a safe procedure even in inoperable patients with multi‐organ failure and cardiogenic shock. In such cases, the heart team should be prepared to proceed to emergent implantation for timely and successful management of the patient.